Maternal Mortality in the Main Referral Hospital in Angola, 2010-2014: Understanding the Context for Maternal Deaths Amidst Poor Documentation - Abubakar Sadiq Umar, MBBS, MPH, MHPM, FWACP; Lusamba Kabamba, MD (Global Health and Education Projects, Inc., 2016)
Background: With the global clamoring for the prevention of pregnancy related maternal deaths and to achieve Millennium Development Goal (MDG 5) by 2015, this work aimed to establish the magnitude and factors associated with maternal mortality in the main referral maternity hospital in Kuando Kubango province of Angola. Methods: The study design was a retrospective analysis of all maternal deaths and deliveries that were recorded from 2010 to 2014. The information collected included data on pregnancy, labour and post-natal period retrieved from case notes and the delivery register. Results: During the period under study, a total of 7,158 live births were conducted out of which 131 resulted in maternal death with an overall maternal mortality ratio of 1,830 per 100,000 live births.  The direct obstetric causes accounted for 51% of all deaths.  The major causes were haemorrhage (15%), puerperal sepsis (13%), eclampsia (11%) and ruptured uterus (10%).  The factors of mutual instability of statistical significance associated with maternal death are: place of domicile (P=0.0001) and distance to the hospital (P=0.0001). Conclusion and Global Health Implication: The study demonstrated that the MMR in maternity hospital is very high and is higher than the WHO 2014 estimates and the province is yet to achieve the desired MDG 5 target by the end of 2015. There is the need for better documentation and periodic reviews all cases of maternal deaths. Key words: Maternal Mortality, Causes, Determinants, Poor Documentation, Angola Copyright © 2016 Umar and Kabamba. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.